Women In Moderating Corporate Social Responsibility - Happy Sista Devy; Arsyad Hukmi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
Making of decision and process in operational companies could not be separated or closely related by shareholders such as the Board of Commissioners and Directors. The Existence of Women Directors Towards Color of nuance in Companies, Several studies determined the existance of Women Directors in Companies tend to change the dynamics in the Companies. The purpose of this study was to discover the effect of corporate social responsibility (CSR) on corporate value and to determine the relationship between female directors in moderating between CSR reporting on company value on Islamic shares in Indonesia. The results showed that coporate social responsibility (CSR) had a positive and significant effect on the price earnings ratio (PER) and return on equity (ROE), and the Women Directors could not moderate the influence of CSR on company value.